The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0104-6632.20140312s00002760
|View full text |Cite
|
Sign up to set email alerts
|

Solubility measurement and solid-liquid equilibrium model for the ternary system MgBr2 + MgSO4 + H2O at 288.15 K

Abstract: -The solubility of magnesium minerals and the refractive index of the ternary system MgBr 2 + MgSO 4 + H 2 O at 288.15 K were investigated using an isothermal dissolution method. It was found that there are two invariant points in the phase diagram and the solubility isotherm of this ternary system consists of three branches, corresponding to equilibrium crystallization of Epsomite (MgSO 4 ·7H Mg,Br,SO ψ at 288.15 K was fitted using the Pitzer theory and Harvie-Weare (HW) approach. In addition, the average eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Figure shows the comparison concerning the solubilities for the ternary MgBr 2 –MgSO 4 –H 2 O system at 273.15, 288.15, 298.15, 308.15, 323.15, 333.15, and 348.15 K. These solubility curves show nearly the same tendency. There is a gradual fall in the solubility of MgSO 4 with the increasing solubility of MgBr 2 at any temperature given.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Figure shows the comparison concerning the solubilities for the ternary MgBr 2 –MgSO 4 –H 2 O system at 273.15, 288.15, 298.15, 308.15, 323.15, 333.15, and 348.15 K. These solubility curves show nearly the same tendency. There is a gradual fall in the solubility of MgSO 4 with the increasing solubility of MgBr 2 at any temperature given.…”
Section: Resultsmentioning
confidence: 75%
“…The main information associated with the crystallization regions and invariant points is imperfect, which could not be used to design an effective separation process. To overcome these shortcomings, the solubilities of this system have been investigated at 288.15, 323.15, and 333.15 K for the extraction of bromine from bittern in recent years. It is found that the solubility of MgBr 2 and the dry salt percentage of MgBr 2 at invariant points increase with the increasing temperature, which means that the purity of the MgBr 2 product tends to be higher. Currently, the largest dry salt ratio of MgBr 2 at the invariant point is only 98.44% at 333.15 K, which is not satisfactory for the high-purity standard of the MgBr 2 product.…”
Section: Introductionmentioning
confidence: 99%
“…The early reports on equilibrium solubilities of the ternary systems LiI–LiBr–H 2 O and NH 4 Br–LiBr–H 2 O at 298.2 K stemmed from Tang et al For the Western Sichuan Basin (in China) brine-salt complex multicomponent system Na–K–B 4 O 7 –Br–Cl–SO 4 –H 2 O, Sang’s research group has done a lot of studies on subsystems NaBr–Na 2 SO 4 –H 2 O and KBr–K 2 SO 4 –H 2 O at 348.15 K and NaBr–KBr–Na 2 SO 4 –K 2 SO 4 –H 2 O and Na 2 B 4 O 7 –Na 2 SO 4 –NaBr–H 2 O at 298.15, 323.15, and 348.15 K. Dan, Yang, Meng et al fitted the ion-interaction parameters in the ternary system MgBr 2 –MgSO 4 –H 2 O at 288.15, 323.15, and 333.15 K and calculated the corresponding solubilities. Christov established a new chemical model to calculate the phase equilibrium data of the system Na–K–Mg–Ca–Br–SO 4 –H 2 O, and the results were satisfactory.…”
Section: Introductionmentioning
confidence: 99%